lncRNA OR3A4 Promotes the Proliferation and Metastasis of Ovarian Cancer Through KLF6 Pathway - Guo, Fangfang; Du, Jianan; Liu, Lingling; Gou, Yawei; Zhang, Mingming; Sun, Wei; Yu, Hongmei; Fu, Xueqi (Frontiers in Pharmacology, 2021)
Aim: Ovarian cancer is a collaborative malignant tumor of the female reproductive system in clinical research. Some clinical studies have shown that OR3A4, which is a cancer-causing lncRNA, plays a major role in promoting the occurrence and development of a variety of tumors. And we also expressed the view that it expressed in ovarian tissue. However, the function of OR3A4 in ovarian cancer remains unclear. Methods and Results: To further verify the function of lncRNA OR3A4 in ovarian cancer, we established the xenograft model in the zebra fish. In this study, cells transformed with OR3A4 shRNA plasmids were transplanted into the zebra fish, and the cell proliferation and migration ability were significantly reduced compared to the empty vector. While knocking out OR3A4, we further downregulated its expression by siRNA of KLF6. Our study found that the knocked out OR3A4 resulted in a decrease in cell proliferation and migration level, which can be found in the downregulated expression of KLF6. We also verify the relationship between OR3A4 and circulating tumor cells in the zebra fish xenograft model, the results indicate that lncRNA OR3A4 may be involved in the resistance of ovarian cancer to complain. Conclusion: lncRNA OR3A4 promotes the proliferation and metastasis of ovarian cancer through the KLF6 pathway.